The burden of mental disorders, substance use disorders and self-harm among young people in Europe, 1990-2019: findings from the Global Burden of Disease Study 2019 - Castelpietra, Giulio; Knudsen, Ann Kristin Skrindo; Agardh, Emilie E.; Armocida, Benedetta; Beghi, Massimiliano; Iburg, Kim Moesgaard; Logroscino, Giancarlo; Ma, Rui; Starace, Fabrizio; Steel, Nicholas; Addolorato, Giovanni; Andrei, Catalina Liliana; et al. (The lancet. Regional health, 2022)
Background - Mental health is a public health issue for European young people, with great heterogeneity in resource allocation. Representative population-based studies are needed. The Global Burden of Disease (GBD) Study 2019 provides internationally comparable information on trends in the health status of populations and changes in the leading causes of disease burden over time. - Methods - Prevalence, incidence, Years Lived with Disability (YLDs) and Years of Life Lost (YLLs) from mental disorders (MDs), substance use disorders (SUDs) and self-harm were estimated for young people aged 10-24 years in 31 European countries. Rates per 100,000 population, percentage changes in 1990-2019, 95% Uncertainty Intervals (UIs), and correlations with Sociodemographic Index (SDI), were estimated. - Findings - In 2019, rates per 100,000 population were 16,983 (95% UI 12,823 - 21,630) for MDs, 3,891 (3,020 - 4,905) for SUDs, and 89·1 (63·8 - 123·1) for self-harm. In terms of disability, anxiety contributed to 647·3 (432-912·3) YLDs, while in terms of premature death, self-harm contributed to 319·6 (248·9-412·8) YLLs, per 100,000 population. Over the 30 years studied, YLDs increased in eating disorders (14·9%;9·4-20·1) and drug use disorders (16·9%;8·9-26·3), and decreased in idiopathic developmental intellectual disability (-29·1%;23·8-38·5). YLLs decreased in self-harm (-27·9%;38·3-18·7). Variations were found by sex, age-group and country. The burden of SUDs and self-harm was higher in countries with lower SDI, MDs were associated with SUDs. - Interpretation - Mental health conditions represent an important burden among young people living in Europe. National policies should strengthen mental health, with a specific focus on young people. - Funding - The Bill and Melinda Gates Foundation